A single tillage in a long‐term no‐till system on dryland crop performance. (3rd June 2020) - Schlegel, Alan; Holman, Johnathon D.; Assefa, Yared
Abstract: A no‐till system may cause stratification of soil organic C and lack effective control of herbicide‐resistant weeds. An occasional tillage is proposed to alleviate these, but only limited information is available on the effect of a single or occasional tillage on crop yield in a no‐till wheat grain−sorghum−fallow (WSF) rotation. The objective of this research was to determine the effect of a single tillage to a 10‐cm depth of a long‐term (>6 yr) continuous no‐till WSF system on grain yield, soil water, and water use of grain sorghum ( Sorghum bicolor L.) and winter wheat ( Triticum aestivum L.) for up to 3 yr after the single tillage operation. This research was conducted at Garden City and Tribune, KS. The three tillage treatments were a single tillage in May or June during fallow (June tillage), a single tillage after wheat harvest (July tillage), and a complete NT system. Grain yield of sorghum varied from average of 3.40 Mg ha −1 at Garden City in 2014 to 8.04 Mg ha −1 at Tribune in 2016. Grain yield of winter wheat varied from average of 0.47 Mg ha −1 at Garden City in 2014 to 5.21 Mg ha −1 at Tribune in 2016. There was no significant effect from a single tillage (June tillage or July tillage) on crop yield, yield components, biomass, available soil water (ASW), and water use compared with continuous no‐till. Therefore, we have concluded that a single tillage of a long‐term no‐till dryland WSF system can be done without affecting crop performance.